2013
DOI: 10.2196/jmir.2198
|View full text |Cite
|
Sign up to set email alerts
|

A Field Test of Web-Based Screening for Dry Eye Disease to Enhance Awareness of Eye Problems Among General Internet Users: A Latent Strategy to Promote Health

Abstract: BackgroundA Web-based self-check system including a brief questionnaire would seem to be a suitable tool for rapid disease screening.ObjectiveThe purpose of this preliminary study was to test a Web-based self-screening questionnaire for drawing attention to dry eye disease among general Internet users and identifying those with a higher risk of developing the condition.MethodsA survey website was launched and used to recruit participants from general Internet users. In the first phase, volunteers were asked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…Ocular symptoms such as eye dryness, eye strain, and blurry vision are symptoms commonly reported by VDT users [ 22 ]. A large-scale epidemiologic study amongst office workers in Japan recently showed that VDT work is an important risk factor for DED [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ocular symptoms such as eye dryness, eye strain, and blurry vision are symptoms commonly reported by VDT users [ 22 ]. A large-scale epidemiologic study amongst office workers in Japan recently showed that VDT work is an important risk factor for DED [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ocular symptoms such as dryness, eyestrains, and blurry vision are commonly reported symptoms related to visual display terminal (VDT) users. 10 VDT exposure has been increasing among office workers because of the rapid advancement of information technology. A recent large-scale epidemiologic study of office workers in Japan concluded that VDT work is considered one of the key risk factors for DED.…”
Section: Introductionmentioning
confidence: 99%
“…In a web-based screening for DED study carried out on 1689 computer users aged 20 years and above, 36.2% of participants reported 5 or more dry eye symptoms. The participants that had symptoms of dry eye were investigated with schirmer test and 32.2% of them had abnormal tear production [20].…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, in the United States of America, a population-based survey on prevalence of dry eye among mid-aged and above, 39,876 women participating in the Women's Health Study showed the prevalence of DED to be 5.7% among women less than 50 years old and 7.8% among women greater than 50 years [20].…”
Section: Discussionmentioning
confidence: 99%